Equity‐Based Compensation of Outside Directors and Corporate Disclosure Quality1. (22nd January 2015) - Sengupta, Partha; Zhang, Suning
Abstract We examine the relationship between a firm's disclosure quality and equity‐based compensation of independent members of the board of directors. The dimensions of disclosure quality we focus on are management's earnings guidance and information flowthrough financial analysts. Using both levels and changes specifications, we find the average ratio of equity‐based pay to total pay of independent board members to be positively related to a firm's disclosure quality. Our findings are robust to the inclusion of management's equity‐based compensation, other governance measures, and financial controls, and robust to instrumental variable tests of endogeneity. Furthermore, we find directors' equity‐based compensation to be negatively associated with the firm's cost of equity capital. Our results are consistent with equity‐based compensation providing incentives to independent directors to push for better disclosure quality.